2010
DOI: 10.1590/s1519-566x2010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Morfología de los estados inmaduros y adulto de Neohydatothripsdenigratus (De Santis) (Thysanoptera: Thripidae), con datos sobre su biología

Abstract: -The adult female of Neohydatothrips denigratus (De Santis) is redescribed, the male and immature stages (larva, prepupa and pupa) are described for the fi rst time, and aspects of the biology of this species are made known. Descriptions of the different stages of development were made from laboratory-reared specimens on using twigs of Phaseolus vulgaris as a feeding and oviposition substrate. Neohydatothrips denigratus undergoes its life cycle on the leaves of P. vulgaris, no immature stages were found in fl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The metanotal striae are similar to those of N. gracilipes and not closely set, with no markings or shadow lines associated with the major striae. N. burungae was found in large numbers on avocado leaves in Mexico and Guatemala (Hoddle et al 2002), and Contreras and Zamar (2010) indicated that the species breeds on Medicago sativa, Phaseolus vulgaris and Solanum esculentum in Argentina (Table 1).…”
Section: Neohydatothrips Aztecusmentioning
confidence: 99%
“…The metanotal striae are similar to those of N. gracilipes and not closely set, with no markings or shadow lines associated with the major striae. N. burungae was found in large numbers on avocado leaves in Mexico and Guatemala (Hoddle et al 2002), and Contreras and Zamar (2010) indicated that the species breeds on Medicago sativa, Phaseolus vulgaris and Solanum esculentum in Argentina (Table 1).…”
Section: Neohydatothrips Aztecusmentioning
confidence: 99%